Effects Of Octane Rating Of Commercially Available Gasoline Fuel On Engine Performance, Emissions And Combustion Characteristic In Spark Ignition (SI) Engine - Sani, Muhammad Qayum (Universiti Sains Malaysia, 2018)
Gasoline among the most fuel used in transportation sector compares to other fuel. Research to analyze the effect of different gasoline fuel grade or fuel octane rating (RON) on engine performance under a different engine speed has been done. A single-cylinder engine Mitsubishi GM131P horizontal shaft is used for experimental setup. The engine was fueled by three different type of fuel which is RON 95, RON 97 and RON 100 to determine the performance of the engine. This research also analyzes the effect of blending two (binary blend) and three (ternary blend) type of fuel together on the engine performance and emissions. The engine is connected with eddy current dynamometer and controller to measure the force, torque, and power produced by the engine. As for analyzing the emission of gas produce, Autocheck SPTC 5-gas analyzer was used to measure the amount of gas produced by the engine under different condition and an exhaust gas temperature (EGT) sensor is attached at the exhaust of the engine alongside with the gas analyzer probe. Overall, the experimental result shows the engine operates with RON 95 provide a better engine performance, but with higher exhaust emissions of carbon dioxide (CO2), carbon monoxide (CO) and nitrogen oxide (NOx). The usage of ternary fuel blend improves the performance of the engine but not environment-friendly where it produces high formation of CO2, and NOx.